Content Marketing Elements for Search Advertising - Repovienė, Rūta (Socialiniai tyrimai, 2017)
The author analyzes the possibility of using content marketing elements for search advertising from marketing experts and searchers’ perspective. The first part of the paper deals with the theoretical insights into the concepts of content marketing, search advertising, their effect and synergy. The second part is qualitative research on a theoretical model of content marketing elements. The possibility of using those elements and modifying the theoretical model are provided in the third part of the paper. Research results revealed that content marketing elements can be used for search advertising and that they affect search advertising. Conclusions and directions for further research. are provided in the paper.